Cooling the soft tissue and its effect on perception of pain during infiltration and block anesthesia in children undergoing dental procedures: A comparative study - Sagorika Bose; Nishita Garg; Lumbini Pathivada; Ramakrishna Yeluri (Tabriz University of Medical Sciences, 2019)
Background. This study assessed the effect of cooling the soft tissue site on the perception of pain in children undergoing local anesthesia for routine dental procedures. Methods. One hundred children, 6‒14 years of age, were assigned to either of the two study groups, i.e., group 1 (infiltration) and group 2 (block anesthesia). One side of the arch served as the test side, where an ice pretreatment (IP) of the soft tissue of the injection site was carried out using a tube of ice for one minute, whereas the opposite side served as the control, where no ice pretreatment (WIP) was carried out. This was followed by the gradual injection of local anesthetic solution. The children's pain perception was assessed by VAS, WB-FPRS and SEM scales. The data were analyzed statistically. Results. WBS, VAS and SEM scores were significantly different between the WIP and IP in both groups, indicating that ice was effective in reducing the pain perception in children. Intergroup comparison revealed no significant differences (P>0.05), indicating that cooling was equally effective in infiltration and block anesthesia. Conclusion. Cooling the soft tissue site helped decrease pain perception during injection in children.